The Effects of Exercise Using Minnesota Strategy Problem Solving Model to Student Learning Outcomes and Critical Thinking Ability - Merisa, NS; Halim, A; Mahzum, Elmi (Asian Journal of Science Education, 2020)
This study aims to look at the effect of the Physics Problem Solving Exercise by using the "Minnesota Strategy" Problem Solving Model to improve Student Learning Outcomes and Critical Thinking Abilities in SMA 3 Seunagan. The approach used is a quantitative approach in the form of experimental research. Then the data is analyzed using N-gain and t-test. Hypothesis testing used by one-party test that is the right hand side, with criteria accepted by H1 if tcount ttable and H1 is rejected if tcount ttable. Hypothesis test results obtained for student learning outcomes data tcount = 4.18 and ttable = 1.68 and for critical thinking data tcount = 5.09 and ttable = 1.68 then it can be concluded tcount ttable, in other words H1 accepted. The conclusion of this research is that there is an influence on the use of Physics Problem Solving Exercises by using the "Minnesota Strategy" Problem Solving Model to improve Student Learning Outcomes and Critical Thinking Ability.Keywords: Minnesota Strategy, Learning Outcomes, critical thinking skills.